Advertisement Remove all ads

Advertisement Remove all ads

Sum

Solve the quadratic equation x^{2} - 3(x + 3) = 0; Give your answer correct two significant figures

Advertisement Remove all ads

#### Solution

x^{2} - 3(x + 3) = 0

`=> x^2 - 3x - 9 = 0`

Comparing with `ax^2 + by + c` we get

`:. x = (-b+-sqrt(b^2 - 4ac))/(2a)`

`=> x = (-(-3)+- sqrt((-3)^2 - 4(1)(-9)))/(2(1))`

`=> x = (3+- sqrt(9+36))/2`

`=> x = (3+- sqrt45)/2`

`=> x = (3+- sqrt(9xx5))/2`

`=> x = (3+-3sqrt5)/2`

`=> x = (3+3sqrt5)/2 or x = (3-3sqrt5)/2`

`=> x = (3+3xx2.236)/2 or x = (3-3xx2.236)/2`

`=> x = (3+6.708)/2 or x = (3-6.708)/2`

`=> x = 9.708/2 or x = (-3.708)/2`

`=>` x = 4.85 or x = -1.85

`=>` x = 4.9 or x = -1.9

Concept: Quadratic Equations

Is there an error in this question or solution?

Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads